Diretrizes para a atenção oncológica no Estado de São Paulo: contribuições para o debate - M. M. A. Correa, Maria Cecilia; Naffah Filho, Michel; A. M. Cecilio, Mônica (BEPA. Boletim Epidemiológico Paulista, 2011)